Novel insights into Cr(VI)-induced rhamnolipid production and gene expression in Pseudomonas aeruginosa RW9 for potential bioremediation - Arisah, Fatini Mat; Ramli, Norhayati; Ariffin, Hidayah; Maeda, Toshinari; Farid, Mohammed Abdillah Ahmad; Yusoff, Mohd Zulkhairi Mohd (Korean Society for Microbiology and Biotechnology, 2024)
Rhamnolipid (RL) is renowned for its efficacy in bioremediating several types of organic and metal contaminants. Nevertheless, there has been a scarcity of studies specifically examining the relationship between this substance and metals, especially in terms of their impact on RL formation and the underlying interaction processes. This study addresses this gap by investigating the RL mechanism in Cr (VI) remediation and evaluating its effect on RL production in Pseudomonas aeruginosa RW9. In this study, P. aeruginosa RW9 was grown in the presence of 10 mg l-1 Cr (VI). We monitored RL yield, congeners distribution, and their ratios, as well as the transcriptional expression of the RL-encoded genes: rhlA, rhlB, and rhlC. Our results revealed that RL effectively reduced Cr (VI) to Cr (III), with RL yield increasing threefold, although with a slight delay in synthesis compared to control cells. Furthermore, Cr (VI) exposure induced the transcriptional expression of the targeted genes, leading to a significant increase in di-RL production. The findings confirm that Cr (VI) significantly impacts RL production, altering its structural compositions and enhancing the transcriptional expression of RL-encoded genes in P. aeruginosa RW9. This study represents a novel exploration of Cr (VI)'s influence on RL production, providing valuable insights into the biochemical pathways involved and supporting the potential of RL in Cr (VI) bioremediation.